2022
DOI: 10.1021/acs.jafc.2c00206
|View full text |Cite
|
Sign up to set email alerts
|

TetR-Type Regulator Lp_2642 Positively Regulates Plantaricin EF Production Based on Genome-Wide Transcriptome Sequencing of Lactiplantibacillus plantarum 163

Abstract: Whole-genome and transcriptome sequences of Lactiplantibacillus plantarum 163 are provided. There was one circular chromosome and four circular plasmids,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The transcriptomic and proteomic data of L. plantarum 163 under glucose and maltose conditions were determined in a previous study. , The transcriptomic data were obtained from the NCBI database (SRA: SRR12831476), and the proteomic data were obtained from the National Protein Science Center (Beijing, China) (PXD022981). Gene and protein changes in glycolysis, pentose phosphate pathway, tricarboxylic acid cycle, and purine metabolism were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptomic and proteomic data of L. plantarum 163 under glucose and maltose conditions were determined in a previous study. , The transcriptomic data were obtained from the NCBI database (SRA: SRR12831476), and the proteomic data were obtained from the National Protein Science Center (Beijing, China) (PXD022981). Gene and protein changes in glycolysis, pentose phosphate pathway, tricarboxylic acid cycle, and purine metabolism were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…This study identified unique genes and metabolic pathways in L. plantarum K25 that may have potential applications in the fields of probiotics and biotechnology. However, there are still knowledge gaps in our understanding of the genome of L. plantarum K25, particularly in the role of certain genes and the mechanisms underlying its probiotic properties (Zhao et al, 2022). Further research is needed to fill these gaps and fully unlock the potential of Lactiplantibacillus K25 for improving human health and advancing biotechnological research.…”
Section: Introductionmentioning
confidence: 99%